68.5k views
2 votes
Help anyone??????????

Help anyone??????????-example-1
User Musicfuel
by
4.8k points

2 Answers

6 votes

Answer:

x = -2, y = -4

x = -1, y = -1

x = 0, y = 2

x = 1, y = 5

Explanation:

Just apply the formula into the different values for x.

x = -2

y = 3(-2) + 2

= -6 + 2

= -4

x = -1

y = 3(-1) + 2

= -3 + 2

= -1

x = 0

y = 3(0) + 2

= 0 + 2

= 2

x = 1

y = 3(1) + 2

= 3 + 2

= 5

User Jared Barden
by
5.3k points
0 votes
0,1,2,3 :) lol yeh that’s my answer
User Josh Crowder
by
4.5k points